anonymous
  • anonymous
I'm having trouble with these types of problems: -(3y+4)-(-2y-5)=0. I don't know when I'm supposed to change the negative to positive or vice versa. Someone please me!!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
The rules for multiplying positive and negative numbers are the following:\[2 \times 3 = 6\]\[2 \times -3 = -6\]\[-2 \times 3 = -6\]\[-2 \times - 3 = 6\] So you should see, (positive) x (positive) = (positive) (positive) x (negative) = (negative) (negative) x (positive) = (negative) (negative) x (negative) = (positive) If you have two same signs when multiplying, the number is positive. If you have two different signs when multiplying, the number is negative.
anonymous
  • anonymous
So \[-(3y+4)\]means\[-1 \times (3y+4)=-1 \times 3y +-1 \times 4=-3y-4\]
anonymous
  • anonymous
The second part is\[-(-2y-5)=-1 \times -2y+-1 \times -5=2y+5\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
In the first expansion, we had (negative) x (positive) = (negative), and in the second, (negative) x (negative) = (positive).
anonymous
  • anonymous
Combine them to give,\[-3y-4+2y+5=0\]which looks like\[-y+1=0\]after collecting like-terms. Adding y to both sides gives you,\[y=1\]
anonymous
  • anonymous
Does this help?

Looking for something else?

Not the answer you are looking for? Search for more explanations.